A CO2-Switchable Polymer Surfactant Copolymerized with DMAEMA and AM as a Heavy Oil Emulsifier. Issue 8 (2nd August 2016) - Zhou, Zheng; Lu, Hongsheng; Huang, Zhiyu
Abstract : A CO2 -switchable polymer surfactant was synthesized with acrylamide (AM) and 2-(dimethylamino)ethyl methacrylate (DMAEMA). The changes in conductivity, particle size, and ζ-potential were adopted to illustrate its switchability. The CMC of the surfactant was determined by the break point of the curve of surface tension versus concentration. An oil emulsion with 8 g/L surfactant almost reached the highest stability. The thermodynamic stability of the emulsion decreased sharply upon increase of the temperature. Adding an inorganic salt was hard to affect the emulsion stability because the surfactant is non-ionic. The emulsion could maintain its stability even if the concentration of NaCl was as high as 10 g/L. The emulsion could easily be broken by bubbling CO2 . Its dehydration rate was 155 times faster than that without the presence of CO2, and the amount of residual oil in water was only 32.22 ppm, which displayed brilliant performance of de-emulsification. GRAPHICAL ABSTRACT: